2015
DOI: 10.5539/ijbm.v10n3p132
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Work Systems and Proactive Behavior: The Mediating Role of Psychological Empowerment

Abstract: Drawing on social exchange theory, this study explores the relationship between high-performance work systems (HPWS) and proactive work behavior. We also examined whether psychological empowerment mediated the effects of HPWS on employees' proactive behavior. Using a sample of 247 employees employed by three large manufacturing firms in Bangladesh, results from structural equation modeling and hierarchical regression analyses showed that HPWS was positively related to proactive behavior. The results also sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 37 publications
(59 reference statements)
3
38
0
1
Order By: Relevance
“…Some recent studies have provided further evidence of the relationship between HPWS and employee proactivity by assuming that the different HPWS practices may have a joint effect on proactivity. This is the case of Maden (), who demonstrates the relevance of empowerment, competence development and fair reward HR practices on employee proactive behaviour, and Arefin et al (), who find that HPWS, as a whole, have a positive relationship with employee proactive behaviour. Despite these results, more work is needed to understand the processes through which HPWS affect employee proactive behaviour (Maden, ).…”
Section: Hpws As Antecedents Of Employee Proactive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have provided further evidence of the relationship between HPWS and employee proactivity by assuming that the different HPWS practices may have a joint effect on proactivity. This is the case of Maden (), who demonstrates the relevance of empowerment, competence development and fair reward HR practices on employee proactive behaviour, and Arefin et al (), who find that HPWS, as a whole, have a positive relationship with employee proactive behaviour. Despite these results, more work is needed to understand the processes through which HPWS affect employee proactive behaviour (Maden, ).…”
Section: Hpws As Antecedents Of Employee Proactive Behaviourmentioning
confidence: 99%
“…As a result, several authors ( e.g. Arefin et al, ; Caesens et al, ) have suggested that motivational variables should be considered in order to understand why HR practices promote proactivity. Following the suggestions by Parker and colleagues, we will consider two motivational variables to explain the influence of HPWS on employee proactive behaviour, namely, role breadth self‐efficacy (RBSE) – employees' confidence in their ability to successfully fulfil broad roles, and flexible role orientation (FRO) – employees' engagement in broad, open‐ended and interdependent roles (Parker et al, ; Parker, , ).…”
Section: Introductionmentioning
confidence: 99%
“…32 Performance management, employee compensation, flexible work design, and decision-making participation are examples on HR practices that trigger employee proactivity. 10 In a similar line, Beltrán-Martín et al 56 detected a positive link between HR practices and employee proactivity. According to Diamantidis and Chatzoglou, 14 employee proactivity mediated the relationship between organizational and job factors on employee performance.…”
Section: Discussionmentioning
confidence: 86%
“…Research on proactive employee behavior cited numerous antecedents of this construct, e.g. development-oriented performance appraisal, 17 supportive supervision, 11,15 organizational support, learning goal orientation, and job autonomy, 13 psychological empowerment and self-efficacy, 9 high-commitment HR practices, 12 high-involvement HR practices, 16 employee engagement, 32 high-performance work systems, 10 job environment, job autonomy and training culture. 14 The most common variables in this regard were HR practices.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The concept of POS is rooted in the social exchange approach that describes the exchange of both parties with non-binding obligation (Arefin and Raquib, 2015). As noted above, POS meets the employees' socioemotional needs including approval, affiliation and self-esteem (Eisenberger et al, 1990) by providing resources to assist with managing demands of job (Eisenberger et al, 1986).…”
Section: Perceived Organizational Support and Affective Commitment Tomentioning
confidence: 99%